Drivers of racial, regional, and socioeconomic disparities in late‐stage breast cancer mortality. Issue 18 (22nd July 2022) - Moubadder, Leah; Collin, Lindsay J.; Nash, Rebecca; Switchenko, Jeffrey M.; Miller‐Kleinhenz, Jasmine M.; Gogineni, Keerthi; Ward, Kevin C.; McCullough, Lauren E.
Abstract : Background: The authors identified tumor, treatment, and patient characteristics that may contribute to differences in breast cancer (BC) mortality by race, rurality, and area‐level socioeconomic status (SES) among women diagnosed with stage IIIB–IV BC in Georgia. Methods: Using the Georgia Cancer Registry, 3084 patients with stage IIIB–IV primary BC (2013–2017) were identified. Cox proportional hazards regression was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) comparing mortality among non‐Hispanic Black (NHB) versus non‐Hispanic White (NHW), residents of rural versus urban neighborhoods, and residents of low‐ versus high‐SES neighborhoods by tumor, treatment, and patient characteristics. The mediating effects of specific characteristics on the association between race and BC mortality were estimated. Results: Among the study population, 41% were NHB, 21% resided in rural counties, and 72% resided in low SES neighborhoods. The authors observed mortality disparities by race (HR, 1.27; 95% CI, 1.13, 1.41) and rurality (HR, 1.14; 95% CI, 1.00, 1.30), but not by SES (HR, 1.04; 95% CI, 0.91, 1.19). In the stratified analyses, racial disparities were the most pronounced among women with HER2 overexpressing tumors (HR, 2.30; 95% CI, 1.53, 3.45). Residing in a rural county was associated with increased mortality among uninsured women (HR, 2.25; 95% CI, 1.31, 3.86), and the most pronounced SES disparities were among younger women (<40 years: HR, 1.46; 95% CI, 0.88, 2.42). Conclusions: There is considerable variation in racial, regional, and socioeconomic disparities in late‐stage BC mortality by tumor, treatment, and patient characteristics. Précis: There is considerable variation in racial, regional, and socioeconomic disparities in late‐stage breast cancer (BC) mortality by tumor, treatment, and patient characteristics. Understanding specific barriers within patient groups will inform interventions aimed at reducing disparities in late‐stage BC mortality.